Little Cakes and Cookies to Bake - Wheatley, Abigail (Children's Baking Collection, 2013)
This tempting book of bite sized treats is bursting with simple and scrumptious recipes that anyone can cook. You will also find lots of decorating ideas, tips on adapting recipes and allergy advice. Just follow the simple step-by-step instructions to bake small strawberry sponge cakes, shortbread fingers, mini éclairs, lollipop cookies and much more.